Russian Federation Financial Sector Assessment Program : Financial Inclusion - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
The overall state of financial inclusion in Russia is relatively advanced along certain basic metrics. The number of adults with accounts at a financial institution stands at 67.4 percent, which compares well to the Europe and Central Asia (ECA) regional average of 51.4 percent. Account penetration has increased by nearly 20 percentage points since 201l, with increases experienced across all segments of the population, including for the poorest 40 percent and for women.1 Russia also has a large number of regulated financial institutions and enjoys 36.98 branches per 100,000 adults, higher than for the United States (32.39) and China (24.03). In addition, usage of accounts and other financial services remains low among the underserved, as does the available range and quality of financial products and services. The main mode for retail payments is still via cash; while underserved individuals may own accounts, many consumers withdraw the full amount they receive from regular government payments or salaries. Most credit and deposit-taking activity still occurs among the middle-high income segments of the population, and there appear to be gaps in terms of both the availability and usage of appropriate savings products for the underserved. The microcredit products that are available to the underserved are of poor quality. There are low levels of trust in the formal financial sector among the Russian population, in particular for microfinance institutions (MFIs).